Pengaruh Dana Desa, Alokasi Dana Desa, Dan Bagi Hasil Pajak Dan Retribusi Daerah Terhadap Belanja Desa Studi Kasus Pada Desa di Kecamatan Bawang Tahun 2018-2020 - Sinta Nofiana Saputri; Sri Rahayu (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
Village Expenditures are all expenditures that are obligations of the Village in one fiscal year which will not be received back by the Village. From observations, the Central Bureau of Statistics (BPS) of Batang Regency, can be seen that there is a phenomenon in several villages in Bawang District which experienced a decrease in Village Expenditures in Bawang District. This makes Village Expenditures in Bawang District experience a decline in 2019-2020.This study aims to determine the effect of village funds, allocation of village funds, and sharing of regional taxes and retribution on village expenditures, case studies in villages in Bawang District in 2018-2020 either simultaneously or partially. This study uses quantitative methods. The population in this study was all villages in Bawang District. While the sample in this study was 60 data for a period of three years. The data used is sourced from the official website of the Central Statistics Agency (BPS) of Batang Regency. The analytical method used is panel data regression using Eviews 12 Software. The results showed that simultaneously the variables of village funds, allocation of village funds, and sharing of regional taxes and retribution had an effect on village expenditures. While partially, it shows that village funds have an effect on village expenditures, while the allocation of village funds and sharing of regional taxes and retribution has no effect on village expenditures.